To Hear or Not to Hear: Sound Availability Modulates Sensory-Motor Integration - Camponogara, Ivan; Turchet, Luca; Carner, Marco; Marchioni, Daniele; Cesari, Paola (Frontiers in Neuroscience, 2016)
When we walk in place with our eyes closed after a few minutes of walking on a treadmill, we experience an unintentional forward body displacement (drift), called the sensory-motor aftereffect. Initially, this effect was thought to be due to the mismatch experienced during treadmill walking between the visual (absence of optic flow signaling body steadiness) and proprioceptive (muscle spindles firing signaling body displacement) information. Recently, the persistence of this effect has been shown even in the absence of vision, suggesting that other information, such as the sound of steps, could play a role. To test this hypothesis, six cochlear-implanted individuals were recruited and their forward drift was measured before (Control phase) and after (Post Exercise phase) walking on a treadmill while having their cochlear system turned on and turned off. The relevance in testing cochlear-implanted individuals was that when their system is turned off, they perceive total silence, even eliminating the sounds normally obtained from bone conduction. Results showed the absence of the aftereffect when the system was turned off, underlining the fundamental role played by sounds in the control of action and breaking new ground in the use of interactive sound feedback in motor learning and motor development.